2007
DOI: 10.1007/s00436-007-0534-7
|View full text |Cite
|
Sign up to set email alerts
|

Antibody responses in human cystic hydatid disease to the laminated layer of Echinococcus granulosus

Abstract: The laminated layer of hydatid cysts of Echinococcus granulosus represents a considerable amount of parasite material. Its antigenic role, however, is unclear. Extracts of laminated layer taken from sheep cysts were analysed in sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS/PAGE) and were found to contain bands at 55 and 25-29 kDa, which reacted with an anti-sheep IgG antibody probe, indicating that these were likely to be host-contaminating components within the layer. However, the same bands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…IgGs are present in hydatid fluid and some reports suggest the presence of IgGs at the internal face of the cysts (including both germinal and laminar layers) [Coltorti and Varela‐Diaz, 1972, 1975; Varela‐Diaz and Coltorti, 1972, 1973; Shapiro et al, 1992], although this fact was not studied further. Recently, Taherkhani et al [2007] described that in the laminar layer of ovine hydatid cysts proteins with molecular masses of approximately 55 and 25–29 kDa are present that are recognized by antibodies against ovine IgGs. The same proteins were also recognized by a significant proportion of sera from human hydatid patients, particularly by IgG4 antibodies and not by sera from negative control individuals.…”
mentioning
confidence: 99%
“…IgGs are present in hydatid fluid and some reports suggest the presence of IgGs at the internal face of the cysts (including both germinal and laminar layers) [Coltorti and Varela‐Diaz, 1972, 1975; Varela‐Diaz and Coltorti, 1972, 1973; Shapiro et al, 1992], although this fact was not studied further. Recently, Taherkhani et al [2007] described that in the laminar layer of ovine hydatid cysts proteins with molecular masses of approximately 55 and 25–29 kDa are present that are recognized by antibodies against ovine IgGs. The same proteins were also recognized by a significant proportion of sera from human hydatid patients, particularly by IgG4 antibodies and not by sera from negative control individuals.…”
mentioning
confidence: 99%
“…The disease is characterized by the presence of slow-growing, unilocular cysts in various organs of the intermediate host (Taherkhani et al 2007). The immune response produced by hosts, challenged with E. granuclosus eggs or oncosphere, was different at different stages of infection (Li et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that bands with molecular weight of about 55, 25, and 29 kDa of laminated layer reacted with anti-sheep IgG. [32]…”
Section: Discussionmentioning
confidence: 99%